(untitled) (Global Journal of Management and Business Research, 2025)
I Introduction D oes national sovereignty call into question the principle of comparative advantage This is the question we are entitled to ask ourselves in light of the statements and decisions made to end the coronavirus COVID-19 pandemic If we refer to the statements made by French President Emmanuel Macron on 12 March 2020 Angela Merkel on 11 March 2020 and Donald Trump the President of the United States the conclusion is clear In the face of the coronavirus COVID-19 pandemic the disruption of supply chains that is threatening among other things the availability of gels and protective masks in European countries the United States and even the rest of the world means that the development model based solely on the law of markets must be called into question For the French President for example and I quote To delegate our food our protection our ability to care for our living environment to others is madness According to them the consequences of the pandemic prove that it is not always best to follow market forces even when it comes to international trade In so doing the fight against the coronavirus pandemic brings back into fashion the theory of the supremacy of national sovereignty over free trade or at least the application of the principle of comparative advantage for certain goods at least in certain situations Whether it be the protectionist arguments of industrial infancy the arguments of industrial senescence the arguments of strategic goods the arguments of strategic trade policy etc they all have as their backdrop the theory of the supremacy of national sovereignty over the principle of comparative advantage